The views and experiences of lesbians regarding their mental health needs and concerns: qualitative findings from a mixed-methods study - Mc Cann, Edward; Brown, Michael John (My University, 2020)
﻿﻿﻿Purpose: The aim of this paper is to report the specific views and experiences of lesbians and identify their distinct mental health issues and concerns. Design and methods: A mixed-methods design with surveys and individual interviews was utilised. The data were thematically analysed. Findings: The key themes were: (i) enabling service access, (ii) person-centred support, (iii) models of care, (iv) community presence and participation, and (v) future aspirations for mental health services. Practice implications: The study results inform and develops the understanding of the issues that impact upon the mental health and well-being of lesbians. The implications for mental health practice are discussed.
PUBLISHED
Keywords: Lesbian; Nursing; Mental health; Psychosocial needs; Social inclusion; Human rights; Education; Inclusive Society; LGBTQ+; Lesbian; MENTAL HEALTH; PSYCHOSOCIAL; QUALITATIVE RESEARCH; Qualitative methods